(untitled) (Journal of Medical & Health Sciences Review, 2025)
Diabetes Mellitus (DM) is a global metabolic disorder characterized by chronic hyperglycemia. The limitations of synthetic antidiabetic drugs have renewed interest in herbal medicines. This study aimed to develop, standardize, and evaluate a polyherbal formulation (PHF) from Trigonella foenum-graecum (Fenugreek) and Cinnamomum verum (Cinnamon) for the management of diabetes mellitus. The seeds of T. foenum-graecum and bark of C. verum were authenticated, shade-dried, powdered, and mixed in a 3:1 ratio. The PHF was evaluated for organoleptic properties, physicochemical parameters (moisture content, ash values, pH, flow properties), phytochemical constituents, and in-vitro antidiabetic activity (α-amylase inhibition assay). Organoleptic evaluation revealed the PHF to be a brown powder with a characteristic aromatic odor and a bitter taste. Physicochemical analysis showed a moisture content of 6.8±0.02%, total ash value of 7.2±0.03%, and an acidic pH (4.5±0.05). Flow properties were excellent (Angle of repose: 28.5±0.15°; Carr’s index: 12.1±0.5%; Hausner’s ratio: 1.10±0.02). Phytochemical screening confirmed the presence of alkaloids, flavonoids, glycosides, tannins, and saponins. The PHF exhibited significant concentration-dependent α-amylase inhibitory activity with an IC₅₀ value of 48.2 µg/mL, compared to 32.1 µg/mL for Acarbose. The developed polyherbal formulation demonstrated satisfactory physicochemical properties, a rich phytochemical profile, and potent in- vitro antidiabetic activity, suggesting its potential as a stable and effective natural adjunct for managing diabetes mellitus.